Formation of valuable orientations of students of pedagogical higher educational institutions during graphic activity - Savchenko, L.O.; Zenkovich, Yu.O. (Pedagogy of Higher and Secondary Education, 2006)
In article it it opened a problem of formation al students of the pedagogical higher school of vahrahle orientations by way of studying of the fine arts.